Evidence on the formation of singlet oxygen in the donor side photoinhibition of photosystem II: EPR spin-trapping study - Yadav, Deepak Kumar; Pospíšil, Pavel (PloS one, 2012)
When photosystem II (PSII) is exposed to excess light, singlet oxygen ((1)O(2)) formed by the interaction of molecular oxygen with triplet chlorophyll. Triplet chlorophyll is formed by the charge recombination of triplet radical pair (3)[P680(•+)Pheo(•-)] in the acceptor-side photoinhibition of PSII. Here, we provide evidence on the formation of (1)O(2) in the donor side photoinhibition of PSII. Light-induced (1)O(2) production in Tris-treated PSII membranes was studied by electron paramagnetic resonance (EPR) spin-trapping spectroscopy, as monitored by TEMPONE EPR signal. Light-induced formation of carbon-centered radicals (R(•)) was observed by POBN-R adduct EPR signal. Increased oxidation of organic molecules at high pH enhanced the formation of TEMPONE and POBN-R adduct EPR signals in Tris-treated PSII membranes. Interestingly, the scavenging of R(•) by propyl gallate significantly suppressed (1)O(2). Based on our results, it is concluded that (1)O(2) formation correlates with R(•) formation on the donor side of PSII due to oxidation of organic molecules (lipids and proteins) by long-lived P680(•+)/TyrZ(•). It is proposed here that the Russell mechanism for the recombination of two peroxyl radicals formed by the interaction of R(•) with molecular oxygen is a plausible mechanism for (1)O(2) formation in the donor side photoinhibition of PSII.
Keywords: Electron Spin Resonance Spectroscopy; Spinacia oleracea; propylgalan; Free Radicals; fotosystém II (proteinový komplex); Light; uhlík; koncentrace vodíkových iontů; Photosystem II Protein Complex; Singlet Oxygen; světlo; fotochemie; Propyl Gallate; Spin Trapping; Carbon; kyslík; chemické modely; Synechococcus; Photochemistry; Hydrogen-Ion Concentration; spin trapping; elektronová paramagnetická rezonance; Models, Chemical; volné radikály; Oxygen; singletový kyslík